TEACHING WRITING RECOUNT TEXT THROUGH PERSONAL JOURNAL WRITING - Marpaung, Dea Venda; ., Regina; ., Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: This research was conducted to find out whether Personal Journal Writing is effective and how effective it is in teaching writing recount text. This research was conducted to the tenth grade students of SMAN 3 Pontianak in Academic Year 2014/2015. In this research, a quasi experimental design was used by the writer. The samples were class XD as the experimental group and the control group was class XE. In this research, the result of t-test computation was 4.57 with degree of freedom is 65 and t-table is 2.00. It showed that the alternative hypothesis (Ha) that teaching writing recount text through personal journal writing is effective is accepted and the effectiveness was strong. In conclusion, personal journal writing can be a good alternative in teaching writing recount text on the tenth grade students of SMAN 3 Pontianak and in other schools which have similar characteristics to SMA Negeri 3 Pontianak. Â Keywords: Writing, Recount Text, Personal Journal Writing Abstrak: Penelitian ini dilakukan untuk mengetahui apakah Penulisan Jurnal Pribadi efektif dan seberapa efektif Penulisan Jurnal Pribadi dalam mengajar penulisan teks recount. Penelitian ini dilakukan pada siswa kelas 10 SMA Negeri 3 Pontianak tahun ajaran 2014/2015. Metode yang digunakan dalam penelitian ini adalah penelitian quasi-eksperimen. Sampel dari penelitian ini adalah kelas XD sebagai kelompok eksperimen dan kelas XE sebagai grup kontrol. Pada penelitian ini, hasil dari penghitungan uji-t adalah 4,57 dengan derajat kebebasan 65 dan t-table adalah 2,00. Hal ini menunjukkan bahwa hipotesa alternatif yang menyatakan bahwa mengajar penulisan teks recount adalah efektif diterima dan tingkat keefektifitasannya kuat. Kesimpulannya, penulisan jurnal pribadi bisa menjadi alternatif yang baik dalam mengajar menulis teks recount pada kelas 10 SMA Negeri 3 Pontianak dan di sekolah lain yang memunyai persamaan karakteristik dengan SMA Negeri 3 Pontianak. Kata Kunci: Menulis, Teks Recount, Penulisan Jurnal Pribadi